2022
DOI: 10.1177/00420980221114952
|View full text |Cite
|
Sign up to set email alerts
|

The green gentrification cycle

Abstract: Significant research has shown that gentrification often follows the implementation of greening initiatives (e.g. new parks) in cities worldwide, in what scholars have called ‘green gentrification’. A few other studies in the Global North suggest that greening initiatives might be disproportionately located in disadvantaged neighbourhoods that are gentrifying as opposed to disadvantaged areas experiencing continuous disinvestment. Building on these findings, in this critical commentary we present the green gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Furthermore, not all gentrification processes lead to neighborhood upgrades, such as conversions of cleared slums into open spaces in Delhi [34]. Thus, various types of gentrification processes can be distinguished based on their specific processes, for example, slum gentrification [15,35], studentification [36], infrastructure-induced gentrification [37], commercial gentrification [16,38], hybrid gentrification [39], green gentrification [40,41], etc.…”
Section: Slum Gentrificationmentioning
confidence: 99%
“…Furthermore, not all gentrification processes lead to neighborhood upgrades, such as conversions of cleared slums into open spaces in Delhi [34]. Thus, various types of gentrification processes can be distinguished based on their specific processes, for example, slum gentrification [15,35], studentification [36], infrastructure-induced gentrification [37], commercial gentrification [16,38], hybrid gentrification [39], green gentrification [40,41], etc.…”
Section: Slum Gentrificationmentioning
confidence: 99%
“…Example of antagonism: 'Green gentrification' linked to urban greening (Rigolon and Collins 2022) can negatively impact a local community, but may place additional burdens on older people due to economic vulnerability, social exclusion, and other gentrification related forces (Buffel et al 2012).…”
Section: Impact On People (Examples) Impact On Urban Environment (Exa...mentioning
confidence: 99%
“…For this purpose, we choose a rather recent aspect of the northern gentrification debate: green gentrification. Green gentrification, also called environmental or ecological gentrification, is mostly researched in the global North (Blok, 2020;Rigolon & Collins, 2023). It implies the stirring up of gentrification processes through the creation of new parks and greenspaces.…”
Section: Gentrification Debatesmentioning
confidence: 99%
“…Some scholars have indicated that, due to the magnitude and cost of engineering works required to convert wetlands into building lands, permits to develop wetlands are usually given to high-income groups and commercial high bidders (Kuusaana et al, 2021;Munshifwa et al, 2021). Having regard to these insights, we contend that the dynamics of urbanization, wetland encroachment and displacement in African cities is synonymous with the general characteristics of green gentrification in Western cities, which includes urban green spaces, increases in real estate prices, involvement of rich and powerful actors, the rent gap and displacement of vulnerable populations (Anguelovski et al, 2019;Rigolon & Collins, 2023). Interestingly, this relationship has eluded many of the scholars whose research borders on wetland encroachment and green gentrification.…”
Section: Introductionmentioning
confidence: 99%